Effect of Reduced Dietary Crude Protein with Balanced Limiting Amino Acids on Egg Weight and Reproductive Performance of Swarnadhara Layers - Joseph, Beena; Nagaraj, CS (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
A study was conducted in Swarnadhara (SD) layers to find out the effect of reducing crude protein (CP) with supplementation of limiting amino acids to compensate the deficiency of CP. Egg weight and reproductive parameters such as fertility, hatchability, number of saleable chicks and day one old chick weight were studied in 240 SD layers in a completely randomized design in 5 treatments with 6 replications of 8 birds in each. The control diet (T1) was based on corn soy bean meal formulated with 16% CP and 2700 Kcal ME following the ICAR (2013) specifications recommended for improved native chicken breeds. The diets T2 to T5 were made isocaloric to control and composed with 15.5, 15.0, 14.5 and 14.0% CP, respectively. The levels of limiting amino acids namely methionine, lysine, threonine and tryptophan were met as that of control by adding synthetic preparation wherever necessary. Egg weight showed similar effects in all treatments at 32, 36 and 40 weeks of age. Reproductive parameters were recorded in four consecutive hatches and were statistically analyzed. Results showed similar performances in T1, T2, T3 and T5, but were different in T4 in terms of fertility, hatchability and number of saleable chicks. There was no significant difference in progeny chick weight among different treatment groups indicating amino acid supplementation supported equal performance in low CP diets in all the reproductive parameters.
Keywords: Swarnadhara layers; Dietary Crude Protein; Limiting amino acids; Egg weight